Critical Discourse Analysis of News Headlines on Syafri Harto’s Sexual Harassment Case - Jordy Satria Widodo (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
Sexual harassment has been rampantly happening in universities in Indonesia and has become the focus of the government, higher education institutions, and most people in Indonesia to tackle the problem. In actual practice, the victims of this violence do not speak up since they have experienced the epistemic violence over the threats given by the perpetrators. This research dismantles the news construction on Syafri Harto’s sexual violence case in Riau University, Indonesia. The data sources were six news headlines derived from three online news sites, such as cnnindonesia.com, kompas.com, and news.detik.com. The collected data taken were six news titles on Syafri Harto’s sexual harassment case within the university. Moreover, the data analysis took Critical Discourse Analysis (CDA) by Norman Fairclough. The research finding shows that the headlines take diverse syntactical functions and dictions, the sites have different characteristics in producing the news, and the sexual harassment case is seriously discussed as a collective concern.